Geochemistry of the Tigris River basin, Turkey: Spatial and seasonal variations of major ion compositions and their controlling factors - Varol, Memet; Gokot, Bulent; Bekleyen, Aysel; Sen, Bulent (Pergamon-Elsevier Science Ltd, 2013)
A total of 204 water samples were collected from 17 sites in four different water bodies in the Tigris River basin during the period from February 2008 to January 2009. Major ions (Ca2+, Mg2+, Na+, K+, HCO3-, SO42-, Cl-, NO3- and SiO2), water temperature, pH, EC and TDS were determined, and consequently analysis of variance, correlation analysis, cluster analysis, factor analysis and principal component analysis were performed to explore their spatial and seasonal variations, quantify the geochemical and anthropogenic processes and identify factors influencing the ionic concentrations. The results indicated that waters in the Tigris River basin are mildly alkaline with high concentrations of Ca2+ and HCO3-, which in total account for approximately 78% of the total ionic budgets. All parameters studied in the Tigris River showed significant spatial variations, while EC, TDS, Cl-, SO42-, Na+, Ca2+, Mg2+ and HCO3- had significant spatial variations in the dam reservoirs. In the Tigris River, EC, TDS, SiO2, Ca2+ and Mg2+ displayed higher values in months of the dry season, while higher values for pH, NO3-, Cl-, SO42-, Na+, K+ and HCO3- in months of the wet season. In the dam reservoirs, all parameters studied except pH showed higher values in months of the wet season. The major ion chemistry of Tigris River basin is mainly controlled by rock weathering with HCO3- and Ca2+ dominating the major ion composition because of the abundance of carbonate rocks in the basin. A comparison with WHO standards for drinking water indicates that the basin has high-water quality. (C) 2013 Elsevier Ltd and INQUA. All rights reserved.
Keywords: Weathering Processes; Precipitation Chemistry; Element Chemistry; Amazon; System; China; Phosphorus